The Relationship Between Recreational Exercise Frequency And Physical Fitness Level (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the relationship between the frequency of recreational exercise and physical fitness levels through a literature study of various scientific sources. Modern passive lifestyles have led to a decline in physical activity among the public, which contributes to declining fitness levels and increases the risk of non-communicable diseases. Recreational sport, as a voluntary and enjoyable physical activity, has been shown to improve various components of physical fitness if practised regularly. Analysing 10 scientific articles, the results of this study show that the frequency of recreational exercise is positively associated with improvements in physical fitness, including heart-lung endurance, muscle strength and flexibility. Recommendations from the WHO and various studies support the importance of doing at least 150 minutes of physical activity per week. Therefore, recreational exercise done consistently can be an effective solution to improve physical fitness. These findings emphasise the importance of building an exercise habit into daily life.